GUIDELINES FOR APPLYING BUDDHIST PRINCIPLES TO APPROPRIATE PERSONAL CONDUCT IN ACCORDANCE WITH THE NATIONAL STRATEGY ON HUMAN RESOURCE DEVELOPMENT AND CAPACITY BUILDING - Panjan, Wanchai; Chuacharoen, Orathai; Ruangvanit, Passakorn; Chunhasriwong, Kitti; Pradittharom, Anek; Arjareewattana, Walaipon (Journal of MCU Nakhondhat, 2026)
The objectives of this research were: 1) to investigate the application of Buddhist principles to appropriate personal conduct in accordance with the National Strategy on Human Resource Development and Capacity Building; and 2) to formulate guidelines for applying Buddhist principles to appropriate personal conduct aligned with the aforementioned strategy. This study employed a survey research methodology. The sample group consisted of 12,740 participants, selected from the population in each region, with a distribution of 1,820 individuals per region. The research instrument was a questionnaire. Data analysis utilized frequency, percentage, mean, standard deviation, and hypothesis testing (t-test, ANOVA, and Chi-Square). The research findings indicated that: 1) The application of Buddhist teachings for appropriate self-conduct in accordance with the National Strategy on Human Capacity Building and Development accounted for 91.38% of the respondents who actively apply the teachings. Furthermore, among the Buddhist population, the religious principles most frequently applied in daily life were performing duties with honesty and integrity (M = 3.86), followed by consistently recognizing the virtues of oneself and others (M = 3.80), and exhibiting enthusiasm for work or study (M = 3.77), respectively. 2) The appropriate guidelines for applying Buddhist principles to personal conduct in accordance with the National Strategy on Human Resource Development and Capacity Building for the Thai population comprised three approaches: 1) Enhancing knowledge and understanding of Buddhist teachings; 2) Encouraging the population to adhere to Buddhist teachings; and 3) Strengthening the practical application of Buddhist principles among the public.